The ironic state : British comedy and the everyday politics of globalization - Brassett, James (Bristol University Press, 2021)
In this book, James Brassett builds on his prize-winning research to demonstrate how British comedy can provide intimate and vital understandings of the everyday politics of globalization in Britain.